2022
DOI: 10.21203/rs.3.rs-1165475/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Uncertainty Health Risk Assessment and Regional Control of Drinking Water: A Case Study of Hanyuan County, Southwest Mountainous Area, China

Abstract: To evaluate the health risks of drinking water in Hanyuan County, 96 samples of peripheral drinking water were collected from 30 sites in the area. The samples were then analysed for physicochemical properties including Fe, Mn, NH 3 -N, , F-, Pb, Hg, As, Cr 6+ , Cd, and so on. The health risks of ten trace elements in drinking water were probabilistically assessed using the health risk assessment model and Monte Carlo simulation. On this basis, sequential indicator simulations were used to classify the hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…According to the World Health Organization, 80% of diseases worldwide are caused by contaminated drinking water; 50% of the deaths of children around the globe are from contaminated drinking water (12). Research has shown that the health-related quality of life of children and adolescents is affected by height and weight, and children's height and weight are closely related to environmental pollution, especially drinking water pollution, and its impact is inseparable from human life (13).In this study, we quantified the specific effects of perchlorate in drinking water in children and adolescents at each age stage and found that the height and weight of children and adolescents had a dose-response relationship with perchlorate exposure in drinking water, decreased by the influence of perchlorate in drinking water, and had a statistically significant effect on the weight of adolescents aged 6, 7, and 11-14 years, and adolescents aged 11-15 and 18 years.…”
Section: Discussionmentioning
confidence: 99%
“…According to the World Health Organization, 80% of diseases worldwide are caused by contaminated drinking water; 50% of the deaths of children around the globe are from contaminated drinking water (12). Research has shown that the health-related quality of life of children and adolescents is affected by height and weight, and children's height and weight are closely related to environmental pollution, especially drinking water pollution, and its impact is inseparable from human life (13).In this study, we quantified the specific effects of perchlorate in drinking water in children and adolescents at each age stage and found that the height and weight of children and adolescents had a dose-response relationship with perchlorate exposure in drinking water, decreased by the influence of perchlorate in drinking water, and had a statistically significant effect on the weight of adolescents aged 6, 7, and 11-14 years, and adolescents aged 11-15 and 18 years.…”
Section: Discussionmentioning
confidence: 99%